The importance of developing technical creativity in students in technology lessons - Mirjanova Nargiza Norkulovna (Research Parks Publishing LLC, 2021)
The article reveals the theoretical foundations of technical creativity of students. One of the main tasks facing pedagogical science and practice today is the task of developing a creative personality: disclosing the essential forces, creative principles of a personality and creating conditions for their implementation. The role and importance of a creative, proactive and entrepreneurial personality in the framework of the subject